A novel sensitive and fast colorimetric assay for determination of benzidine as a carcinogen aromatic amine based on Bromopyrogallol red. Issue 6 (2nd May 2020) - Tavallali, Hossein; Deilamy-Rad, Gohar; Karimi, Mohammad Ali; Aameri-Siahooei, Mohammad-Aghil
ABSTRACT: Benzidine and its derivatives are among human or animal carcinogens. Therefore, there is an ever-increasing demand for methods suitable for their determination. Herein, we have reported a naked-eye detection method which is based on the benzidine (among carcinogen) reaction with a chromogenic indicator (Bromopyrogallol red (BPR)). The dye-based ensemble systems are expected to be a potential and practical way for the detection of nanomolar concentrations of benzidine in 75% water media. The absorbance signal of BPR increases linearly in the concentration range of 3.25 × 10 −7 –3.34 × 10 −5  mol L −1 for benzidine. The chemosensor enabled sensitive and selective detection of benzidine with a detection limit of 4.17 × 10 −8  mol L −1 . The RSD value (n = 6) of 9.7 × 10 −7 and 3.7 × 10 −6  mol L −1 benzidine was determined to be respectively 2.3% and 2.1%. This process proceeded with distinct visual color change within 1.0 min in aqueous solution. We tested the actual samples successfully, and the measurement results were compared with the gravimetric technique for benzidine. It showed that our method exist no significant difference with standard methods by the Student t -test. Therefore, we provided a rapid, simple, sensitive, accurate, and reliable new method for the determination of benzidine in real samples. Advantages offered by the proposed method, compared with those suggested previously of benzidine determination indicates that they have the second detection limit. This system is simple in design, fast in operation and is more promising than previous methods. This approach eliminated the need for the separation stages, multiple-step reactions, sample preparation, chemical modifications, and sophisticated instrumentations.